ANALISIS LEVEL PERTANYAAN GEOMETRI BERDASARKAN TINGKATAN VAN HIELE PADA BUKU TEKS MATEMATIKA SMP KELAS VII - Ramadhani, Ema Sintia; Sunardi, S; Sri Lestari, Nurcholif Diah (KadikmA, 2013)
Abstrac.: This research aims to determine the percentage of geometry questions for each van Hiele levels in the SMP mathematics textbook for seventh grade, and to determine the percentage of geometry questions for each descriptors in the SMP mathematics textbook for seventh grade based on van Hiele levels. Sources of data in the study include documents geometry questions in the SMP mathematics textbook for seventh grade, written by Tatag Yuli Eko Siswono and Netti Lastiningsih; and also Atik Wintarti et.al. To analyze the data used descriptive analysis with a qualitative approach. The result of the data analysis shows that are 1176 questions in the mathematics textbooks SMP written by Tatag Yuli Eko Siswono and Netti Lastiningsih; and also written by Atik Wintarti et.al. From the results, the percentage of geometry questions for each van Hiele levels in the mathematics textbook written by Tatag Yuli Eko Siswono and Netti Lastiningsih for Visualization, Analysis, Ordering, and Deduction are respectively 9%, 81.31%, 8.47%, and 0%. Then, in the SMP mathematics textbook written by Atik Wintarti et.al, there are 14,88% in the visualization level; 75,42% in the analysis level; 8,36% in the ordering level; and 0% in the deduction level. However, each SMP mathematics textbook for seventh grade are equally dominated by Analysis level. Then, the geometry questions in the mathematics textbook written by Tatag Yuli Eko Siswono and Netti Lastiningsih is dominated by descriptor 4.b and descriptor 9. But, in the SMP mathematics textbook written by Atik Wintarti et.al is dominated by descriptor 2. Key Words : textbook, geometry questions, van Hiele geometric thinking levels